Efficacy of kukkilchooranam and thaharakottaithailam in karappannoi (eczema) in traditional medcine in Srilanka - Nithiakumar, N.; Nushrath Roshana, M.; Kavitha, K. (Department of Chemistry, Department of Physics, Department of Biochemistry & Biotechnology, Department of Pharmacy Annamalai University, 2020)
Background: Srilankan Traditional Medicine rich in diversity and combination of the Indigenous Medicine of the country DeshiyaChiktsa, Ayurveda, Siddha, and Unani Medicine. While the different system of Medicine all come together to form the body of knowledge that we today refer to as "Srilankan Traditional Medicine". Karappan (Eczema) is a disease condition in Traditional Medicine which skin and caused to inflame/ irritation. It is caused by excessive intake of Kiranthi foods like fish, mutton, prawn, cuttle fish, crab, low grade food materials like varagu, thinaii, rhizome, living in hot and cool weather, some poisonous bites, hereditary and contact of allergens like cosmetics, plants, hard soaps, detergents. In books Siddha Maruththuvam (specail), Agasthiyar 2000 and Pararasasegaram the following symptoms are mentioned for KarappanNoi. There are itching, redness, inflammation, vesicle, secondary infection, pustules, hyperpigmentation, hyper keratinization, and scaling skin. In wet type itching followed with vesicles, oozing, and then hyper pigmentation and only in later stage keratinization. KukkilChooranam and ThaharakottaiThailam are using to cure the KarappanNoi by the traditional Doctor Mrs. M.Pathmanathan, on her 3rd generation since 1937. Methods: Two hundred and seventy patients who had this symptom of KarappanNoi who attended E.M Siddha Ayurveda Clinics conducted in Ampara district, Kalmunai town, and Karaitivupiradeshasabah were selected for the study from 23.08.2017 to 25.11.2017 (3 months). The collected data were statistically recorded and analysis made. Results: According to the analysis the signs and symptoms in 64% of those used only this chooranam started gradually disappearing.It was seen reduce the sign and symptoms to 48% of those took only the ThaharakottaiThailam for external use. The sign and symptoms in 93% of those who took this chooranam for internal use and ThaharakottaiThailam for external use started gradually disappearing. The above all three groups observed under the diet restriction. But 5 of the group 2 and 3 patients could not continue with the treatment as the Thaharakottaithailam was increased this Therefore, karappannoi.Conclusion: KukkilChooranam and ThaharakottaiThailamare the best healer for karappannoi. These ingredients can be get anyone and there was a very small percentage of adverse effect observed by using of these medicines. Hence the karappannoi can be kept under control by using these medicines.